GONADOSOMATIC INDEX TIKUS JANTAN (Rattus norvegicus) SETELAH PAPARAN EKSTRAK DAUN MIMBA (Azadirachta indica) SEBAGAI SENYAWA ANTIFERTILITAS - Alam Rivky Saputra; Agung Janika Sitasiwi; Tyas Rini Saraswati (Jurnal Pro-Life, 2020)
Neem leaves is one part of the neem tree (Azadirachta indica) containing antifertility compounds which can suppress the rate of male rat reproduction. The purpose of this study is to examine Gonadosomatic Index after exposure of neem leaves ethanol extract as antifertility compounds. This study is an experimental study with a Completely Randomized Design (CRD), using 12 male rats devided into 4 treatment groups and 3 replications. P0 is a control with aquades treatment, P1, P2, and P3 (neem leaves ethanol extract with each dose of 60, 80, and 100 mg/kgBW/day). The treatment was administered orally wiht a volume of 1 ml for 14 days. The main parameters are testicular weight, body weight and GSI. Body weights were measured every 7 days. Surgery was done after the treatment ends for measuring testicular weight and testicular isolation continued by measuring GSI values. GSI value is determined from body weight and testicular weight. The results were analysed using ANOVA at 95% confidence level. The analysis results showed that there were no significant differences (P>0.05) in the body weight and testicular weight parameters, but there were a significant different (P<0.05) in GSI values. The test results of GSI values show the different decrements in the treatment of P2. Based on the results of the test, it could be concluded that the exposure of neem leaves ethanol extract at doses of 60, 80, 100 mg/kgBW/day for 14 days of exposure time can cause antifertility effect in male rats. Keywords: Neem leaves, GSI, rat reproduction, body weight, testicular weight.